Impacto da adoção das IFRS no custo de capital próprio das empresas brasileiras de capital aberto listadas na B3 - Daniel Rennó Tenenwurcel (2019)
This work analyzes whether the mandatory adoption of the International Financial Reporting Standards (IFRS) by the Brazilian public companies listed in B3 resulted in a decrease in information asymmetry and in the cost of equity. The literature considers that the international accounting standards represent an improvement in the quality of financial information disclosed by companies. Three ways in which IFRS can affect the cost of capital can be highlighted: by reducing non-diversifiable risk, since it improves forecast of future cash flows; by reducing informational asymmetry between well-informed traders and those seeking liquidity; by reducing agency costs, since it improves the alignment between managers and investors. The work tested the hypotheses that the adoption of IFRS decreased the cost of equity because it reduced the information asymmetry, it reduced the non-diversifiable risk of the market and it reduced the diversifiable risk of the companies linked to the reduction of information asymmetry and of the agency costs. In order to reach the objectives, three econometric models were used. First, a proxy for market informational asymmetry, the bid-ask spread, was regressed by the dummy to the adoption of international standards and it was verified that there was a reduction of informational asymmetry in Brazilian publicly traded companies since the adoption of IFRS. In a second step, a portfolio analysis was carried out using a CAPM model and the three-factor model of Fama and French (1993), which pointed out a non-diversifiable risk reduction with the adoption of IFRS and that the three factors model of Fama and French (1993) probably captures this effect. Finally, the company's annualized returns were used as a proxy for the cost of equity and regressed by the bid-ask spread, non-diversifiable risk premium and a dummy variable for the adoption of IFRS. The results do not allow affirming that the IFRS adoption had effects in reducing the diversifiable risk of the companies, either through reduction of information asymmetry or through reduction of agency costs.